STUDIES ON THE EFFECTS OF KOPSIA FRUTICOSA ON MEAN ARTERIAL BLOOD PRESSURE OF ANAESTHETIZED CATS - Munshi, *Santanu; Bhattacharya, Dipankar; Santra, Ranjita; Sur, Tapas (International Journal of Ayurveda and Pharma Research, 2017)
Introduction: Kopsia fruticosa,a member of the Apocynaceae family contains four indole alkaloids whose pharmacological effects have not been extensively studied (Fig. 1-3). Drugs bearing indole alkaloids are known to produce important pharmacological effects. It has been reported that most of the indigenous plant having indole alkaloids exhibit varieties of pharmacological actions on the CVS like hypotension, dilatation of both peripheral and coronary vessels and antileukaemic effect etc. Materials and methods: Hence it was conceived that the compounds of Kopsia fruticosa (KF) may produce some interesting pharmacological actions especially on the cardio-vascular system. The crude extract was prepared from the dried leaves in laboratory and the chief objective of this study was to evaluate the possible effects of both the propylene glycolic (KF1) and the aqueous solution (KF2) of the crude extract of dried leaves of Kopsia fruticosa. Results: Kopsine, one of the alkaloids obtained from the plant Kopsia fruticosa, possesses cholinergic action. This study on the mean arterial blood pressure and respiration of anaesthetized cats consistently revealed that both KF1 and KF2 induce a dose dependent fall in blood pressure, with slight bradycardia and little stimulatory effect on the respiration. Conclusion: Both the solutions, KF1 and KF2 had potent depressor effect on the mean arterial blood pressure of anaesthetized cats.